2023
DOI: 10.1002/adsu.202300205
|View full text |Cite
|
Sign up to set email alerts
|

Milestones of Electrocatalyst Development for Direct Alcohol Fuel Cells

Abstract: With increasing energy demands and environmental issues, renewable energy‐related conversion systems have gained significant attention as a potential substitute for traditional fossil fuel‐based energy technologies. First introduced by S.W.Grove in 1838, fuel cells have been extensively developed into many different types, and direct alcohol fuel cells (DAFCs) are of interest as a potential power source because of their large power density, quick start, simplicity, and nearly zero emission. However, the high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 305 publications
(174 reference statements)
0
2
0
Order By: Relevance
“…1 In this regard, electrochemical oxidation of formate and alcohols is of great interest: (1) Direct formic acid or alcohol fuel cells for electricity generation. 2–6 While significant attention has been placed on H 2 fuel, liquid carbon fuels derived from CO 2 or biomass resources offer several advantages, including higher volumetric energy densities, easier storage and transportation, and compatibility with established infrastructure. 7,8 The direct use of formic acid or alcohol fuels is complementary to their indirect use as H 2 carriers for onboard H 2 delivery, 9,10 although fugitive H 2 emissions are mitigated by the direct approach.…”
Section: Introductionmentioning
confidence: 99%
“…1 In this regard, electrochemical oxidation of formate and alcohols is of great interest: (1) Direct formic acid or alcohol fuel cells for electricity generation. 2–6 While significant attention has been placed on H 2 fuel, liquid carbon fuels derived from CO 2 or biomass resources offer several advantages, including higher volumetric energy densities, easier storage and transportation, and compatibility with established infrastructure. 7,8 The direct use of formic acid or alcohol fuels is complementary to their indirect use as H 2 carriers for onboard H 2 delivery, 9,10 although fugitive H 2 emissions are mitigated by the direct approach.…”
Section: Introductionmentioning
confidence: 99%
“…Alloying Pt with Ru is one of the most well-known and advanced nanomaterials to address detriments (i.e., CO poisoning, sluggish reaction kinetics, etc.) of the commercially available C-supported Pt catalyst for the anodic methanol oxidation reaction (MOR) process in direct methanol fuel cells, which are a potential substitute power source for energy-related applications. In the PtRu catalyst system, Ru sites are more active than Pt in the water-discharge process at a negative potential to form hydroxyl groups, serving as activators to boost the CO ads oxidation step on Pt active sites, thereby releasing more Pt surface and enhancing the MOR rate. In addition, Abruña et al reported that the interatomic distance between Pt and neighboring Ru atoms played an important role in an efficient interaction between Pt-CO ads and Ru–OH ads species to generate a transition state (Pt-CO ads ···OH ads -Ru) for the oxidation of the CO ads during the MOR . Although the PtRu catalyst can reduce the Pt content and enhance the overall MOR efficiency, their electrochemical durability is restricted by the component leaching in strongly acidic media. , Also, Ru metal belongs to the Pt-group metal, which is a major challenge for the widespread commercialization of the PtRu catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…As a cheap fuel, methanol can be used in a Direct Methanol Fuel Cells (DMFCs) to produce energy for portable devices [5][6][7], following a complex mechanism of the Methanol Oxidation Reaction (MOR) by which six electrons are released. In this context, the development of a new class of catalysts able to efficaciously convert the methanol and to work as an anode in the DMFC device and, at the same time, to be highly active, to have a low price, and to have good stability is one of the challenges of the scientific community [8][9][10][11][12]. The standard catalyst commonly used for methanol oxidation is platinum (Pt) [13][14][15] but, unfortunately, the Pt catalyst surface is rapidly poisoned leading to a decrease in the catalysts active surface [16,17].…”
Section: Introductionmentioning
confidence: 99%